Assessment of measurement characteristics for rehydration of milk protein based powders. (March 2016) - Ji, Junfu; Fitzpatrick, John; Cronin, Kevin; Crean, Abina; Miao, Song
Abstract: Rehydration is an important powder property and is regarded as a critical issue by the dairy industry. Traditional powder rehydration measurements are relatively empirical with poor reproducibility. Thus, more reliable techniques tailored for dairy powders should be developed based on varied rehydration behaviours and applications. In this paper, a critical assessment to identify the measurement characteristics of milk protein powder rehydration is presented. Milk protein based powders were used as model systems. Four different wettability measurements (Immersion, Capillary rise, Condensation and Spreading) and four different dispersibility measurements (Dispersibility Index, Light scattering of particles in suspension, Light transmission and Conductivity of suspension) are compared and analysed. The results show that the method based on immersional wetting procedure is only appropriate for skimmed milk powder while the method for capillary rise wetting is more useful for the agglomerated milk protein powders with porous structures. Contact angle changes in the spreading wetting approach is found to be a straightforward technique to show the hydrophobicity or hydrophilicity of milk protein powders. If compared with traditional dispersibility measurements, light transmission of suspension is suitable to reflect optical properties of slow dispersion process. Light scattering methods can also be used to measure the dynamic size change of particles during the dispersion process. Furthermore, the conductivity of suspensions is a useful indicator to quantify the dispersibility indirectly by the release of minerals during rehydration. In summary, it is necessary to understand the specialities and applications of dairy powders before choosing the appropriate rehydration measurement methods. Graphical abstract: Highlights: Milk protein powders exhibit different wetting and dispersing behaviours. Contact angle is most suitable method for assessing wettability. Capillary rise is another useful method to quantify the wettability. Dispersibility of protein powders can be evaluated by the change of particle size. Light transmission of suspension can measure both dispersibility and solubility.